2011
DOI: 10.1007/s11430-011-4181-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of simulated short-range high-temperature weather to land surface schemes by WRF

Abstract: The simulations of a heat wave occurring in southern Yangtze-Huaihe valley and southern China during late July, 2003 were conducted to examine the sensitivity of simulated surface air temperature (SAT) to different land surface schemes (LSSs) using the Weather Research and Forecasting Model (WRF) Version 2.2 in the short-range mode for 24-h integrations. Initial and boundary conditions employed a National Centers for Environmental Prediction (NCEP) analysis. The results showed that, overall, simulated high-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…For example, over 0900–1400 LT, the 850‐ and 700‐hPa heights decrease with the SAT increase, which is consistent with the negative feedback in the lower troposphere (i.e. Zeng et al ., ; ZWZ14), and the 300‐hPa height increases, which also agrees well with the positive feedback in the upper troposphere (e.g. ZWZ14).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For example, over 0900–1400 LT, the 850‐ and 700‐hPa heights decrease with the SAT increase, which is consistent with the negative feedback in the lower troposphere (i.e. Zeng et al ., ; ZWZ14), and the 300‐hPa height increases, which also agrees well with the positive feedback in the upper troposphere (e.g. ZWZ14).…”
Section: Resultssupporting
confidence: 79%
“…Following Zeng et al . () and ZWZ14, for the simulation period we chose the hottest phase of the summer, i.e. late July 2003, when extremely high temperatures occurred over the land of south‐eastern China (within area ‘D2’; Figure S1).…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Sato and Xue (2013) found that different descriptions of land surface processes in various schemes are one major source of uncertainties for the EASM downscaling. Zeng et al (2011) evaluated the sensitivity of simulated shortrange high-temperature weather to LSP schemes by WRF. However, few studies have been done on the evaluation of RCM to multi-LSP schemes for long-term simulation of the EASM comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Weather Research and Forecasting (WRF) has been adapted for simulating regional climate in recent years. With the land surface model embedded in the model, it can show the meteorological features such as diurnal cycle of temperature (Zeng et al 2011) and precipitation, etc., as well as express the influences of regional issues in better resolution to give better understanding of the coupling relationship between land and atmosphere (Das et al 2011;Subin et al 2011).…”
Section: Introductionmentioning
confidence: 99%